Effects on antioxidant responses, stress indicator and immune responses of olive flounder, Paralichthys olivaceus raised in bio-floc culture or seawater culture challenged by Streptococcus iniae - Saebom Sohn; A-Hyun Jo; Cheol Young Choi; Ju-Chan Kang; Jun-Hwan Kim (Comparative Immunology Reports)
Olive flounders, Paralichthys olivaceus (mean weight 1,027 ± 65 g, mean length 44.03 ± 3.1 cm) were raised in bio-floc culture or seawater culture for 10 months. The P. olivaceus raised in bio-floc culture or seawater culture were inoculated at each S. iniae concentrations at 0, 3.36 × 106, 3.36 × 107, 3.36 × 108, and 3.36 × 109 CFU/g fish for 96 h. In antioxidant responses, SOD, CAT and GST activities were significantly increased, whereas GSH level was significantly decreased, with more pronounced changes observed in the seawater culture group. In stress indicators, HSP 70 and cortisol levels were significantly increased in both groups. In immune responses, lysozyme activity and Ig M levels were significantly decreased, with greater reductions in the seawater culture group compared to the bio-floc culture group. These results indicate that S. iniae infection has significant negative effects on antioxidant responses, stress indicators, and immune responses in P. olivaceus, and that these effects are more severe in fish raised in seawater culture than those in bio-floc culture.